Trois enclaves agricoles dans la périphérie de Lyon, vers des agricultures urbaines ? - Rémi Janin (Projets de Paysage)
The agriculture in the Lyon agglomeration seems to be more and more isolated and increasingly enclosed in the urban region. This article is based on three examples located in the Lyon periphery presenting different agricultural forms and situations : one in truck farming in Caluire/Rillieux-la-Pape, one in intensive agriculture in les Grandes Terres/Feyzin and one in breeding bovine farming in Saint-Foy-lès-Lyon. The analysis questions the current status of these agricultural enclaves, their forms and the status of these new farmers. What will become of these spaces : effacement in front of the urban development, agricultural mutation or new agricultures ?